Advancing the Frontiers of Chemical Protein Synthesis—The 7th CPS Meeting, Haifa, Israel. Issue 3 (15th March 2018) - Conibear, Anne C.; Muttenthaler, Markus
Abstract : The 7 th Chemical Protein Synthesis Meeting took place in September 2017 in Haifa, Israel, bringing together 100 scientists from 11 countries. The cutting-edge scientific program included new synthetic strategies and ligation auxiliaries, novel insights into protein signaling and post-translational modifications, and a range of promising therapeutic applications. Abstract : The 7 th Chemical Protein Synthesis Meeting took place in September 2017 in Haifa, Israel, bringing together 100 scientists from 11 countries. The cutting-edge scientific program included new synthetic strategies and ligation auxiliaries, novel insights into protein signaling and post-translational modifications, and a range of promising therapeutic applications.